“Crickets” (Orthoptera) as viewed by the inhabitants of Feira de Santana, Bahia - Dias, Mateus Assunção; Costa Neto, Eraldo Medeiros (SITIENTIBUS série Ciências Biológicas, 2005)
This study aims to record the way “crickets” are perceived by the inhabitants from Feira de Santana, Bahia describing their natural history as viewed by these inhabitants, as well as their semiotic meaning and the possible cultural uses. Data were collected from June to November 2004 using standardized ethnographic techniques. We made open-ended interviews were made with 69 men and 194 women, whose ages ranged from 7 to 79 years old. The interviews were based on a list of previously chosen topics. The information was recorded both in written and micro-cassette recorded registers, with the approval of the interviewed person. What the inhabitants considered “cricket” involved from true crickets (Orthoptera: Gryllidae), grasshoppers (Orthoptera: Acrididae) and katydids (Orthoptera: Tettigoniidae), to praying mantids (Mantodea), beetles (Coleoptera), mosquitoes (Diptera), insects (Insecta), “pests” and “animals”. The inhabitant’s perceptions of these “crickets” were determined by the affective dimension people display for them. In general, feelings, always accompanied by positive or negative impressions, interfere both in the quality and quantity of information. Cognitive data on ethnotaxonomy, seasonality, behavior, food ecology, as well as habitat were recorded. Considering ethnotaxonomy, six kinds of “crickets” were determined by the interviewed inhabitants. The use of the cricket in popular medicine, food, and ludic activities was also recorded. It is concluded that the ethnoentomological knowledge of part of Feira de Santana’s inhabitants and their interaction with “crickets” are culturally mediated.